First record of Chaeteessa nigromarginata from Peru (Mantodea: Chaeteessidae) - Bustamante-Navarrete, Abdhiel (Fragmenta entomologica, 2018)
The second Peruvian record of the genus Chaeteessa Burmeister and the first of the species Chaeteessa nigromarginata Salazar 2004 are reported.